Pengaruh Pemberian Tingkat Konsentrasi Larutan Zat Pengatur Tumbuh Alami Urine Sapi dan Lama Waktu Perendaman Terhadap Perkecambahan Benih Tanjung (Mimusops elengi Linn.) - Maria Yovita Dhone Asten; Astin E. Mau; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Tanjung (Mimusops elengi Linn.) is a good type of plant to be used in various urban forest formation programs due to its many uses. The provision of natural growth regulators (ZPT) from cattle urine, which contains auxin, plays an important role in the growth and development process of a plant and accelerates the initial process of germination and plant growth. The method used in this study (RAL), consisting of two factors: concentration and soaking time. The concentration factor consisted of treatment A0 = control (aquades), A1 = 30% (300ml cattle urine + 700ml aquades), A2 = 60% (600ml cattle urine + 400ml aquades), A3 = 85% (850ml cattle urine + 150ml aquades). The soaking time factor consisted of treatment P0 = control, P1 = 6 hours, P2 = 12 hours, and P3 = 18 hours, with each treatment repeated 3 times, resulting in 48. Each experimental unit required 100 tanjung seeds, so the total of all treatments with repetitions required 4,800. The results showed that the concentration (A) and soaking time (P) of cattle urine had a very significant effect on the germination percentage, germination speed index, and germination value percentage. The treatment of concentration A2 (60% concentration) and the single treatment of soaking time P2 (12 hours soaking) were the best treatments in breaking the dormancy of tanjung seeds. The interaction between concentration and soaking time had a very significant effect on all parameters, namely germination percentage, germination speed index, and germination value of tanjung seeds (Mimosops elengi Linn.).